Revisiting Understanding of The Whistleblowing Concept In The Context of Indonesia - Ilham Nurhidayat; Bevaola Kusumasari (Indonesian Association for Public Administration, 2017)
The conduct of this study came in the backdrop of thinking of the need for opening a discussion for a more comprehensive and contextual concept of whistleblowing for Indonesia from the vantage point of existing theoretical perspectives, regulations and practices. There is a lot of misunderstanding and bias about the concept of whistleblowing in public and private organizations in Indonesia. This study is largely based on previous literature and observation of the implementation of whistleblowing system (WBS) in several institutions that the author considered credible enough to be best practices. The study used descriptive qualitative approach and used various reference sources that were drawn from library research. This research has produced several formulations. First, the synonym or equivalent phrase in the Indonesian language for the term whistleblower is Pengungkap dugaan kecurangan, (revealer of alleged fraud) and Pengungkap dugaan pelanggaraan (revealer of alleged violation) or Pengungkap dugaan perbuatan tidak benar (wrongdoing) (revealer of alleged wrongdoing). Secondly, the most appropriate equivalence to the phrase whistleblowing system (WBS) in the context of Indonesia is “Sistem Pengungkapan Dugaan Pelanggaran” (alleged violation disclosure system). Third, the object of the report or complaints of whistleblowing (wrongdoing) is classifying into seventeen types of behavior that are in turn categorized into seven groups. WBS development and implementation in a number of government and private sector institutions emphasize seven key points. Research findings fill a mainstream research gap on whistleblowing in Indonesia, which has for long been plagued by misunderstanding between WBS and complaints handling system that is evident in several institutions and government agencies in Indonesia. The expectation is that research results will make some contribution to government policy making in the realm of whistleblowing system by providing a definition that is in line with the initial conception of the concept of whistleblowing. That way, this research is expected to contribute to the development of a more effective policy and WBS that not only protects the whistleblower but also pays attention ethics, culture, and local context in Indonesia which are different from the countries where the concept of whistleblowing had its origins.